Religion in the Russian National Security System: An Ontological Security Perspective and the Problem of the (De)Secularisation of Putin’s Russia - Marcin Składanowski (Religions, 2025)
This article examines the role of religion in Russia’s national security system through the lens of ontological security, assessing whether contemporary Russia is undergoing a process of desecularisation or, conversely, an intensified form of secularisation. Employing the theoretical framework of ontological security, this study argues that Russia’s securitisation of religion serves as a mechanism for consolidating state control, legitimising authoritarian governance, and constructing a distinct civilisational identity in opposition to Western liberalism. The Russian Orthodox Church, rather than functioning as an autonomous religious institution, has been absorbed into the state apparatus, where it operates as an instrument of state ideology. Religious rhetoric permeates Russian strategic security documents, reinforcing narratives of national exceptionalism, historical continuity, and moral superiority, particularly in justifying Russia’s geopolitical ambitions and military actions, including its war against Ukraine. The analysis challenges prevailing interpretations of religious resurgence in Russia, arguing that the increasing presence of religion in public life does not necessarily signify desecularisation. Instead, the instrumentalisation of religion for political and security purposes suggests a process of extreme secularisation, wherein religious institutions lose their autonomy and doctrinal substance, becoming tools of state power.